A NEW RP-UPLC METHOD FOR THE SEPARATION AND SIMULTANEOUS QUANTIFICATION OF DORZOLAMIDE HCl AND TIMOLOL MALEATE - ELURU, ASHA; BABU, K. SURENDRA (International Journal of Applied Pharmaceutics, 2024)
Objective: This investigation demonstrates a stability-indicating and reliable “reverse-phase ultra-performance liquid chromatography” method to simultaneously quantify timolol maleate and dorzolamide HCl in the pharmaceutical dosage form. Methods: Successful separation was accomplished using Phenyl column (100 mm x 2.1 mm, 1.7μm) with isocratic type of elution using mobile phase containing Acetonitrile+Ammonium Formate buffer (30:70), respectively with 0.2 ml/min flow rate. The wavelength sensor was attuned at 266 nm to quantify timolol maleate and dorzolamide HCl. Results: Dorzolamide HCl and timolol maleate peaks were eluted with fine resolution at retention times 0.7 min and 1.5 min, respectively. In the 55.75-334.5 μg/ml and 6.25-37.5 μg/ml concentration ranges for dorzolamide HCl and timolol maleate, the calibration graphs were linear, with regression coefficients of 0.99997 and 0.99991, respectively. The suggested ultra-performance liquid chromatography approach has been shown as sensitive, precise, robust, accurate, specific and stability, indicating through the resolution of dorzolamide HCl and timolol maleate from its degradation-based compounds. Conclusion: The established ultra-performance liquid chromatography technique was effectively extended to the evaluation of dorzolamide HCl and timolol Maleate in the pharmaceutical dosage form and the test results appeared satisfactory.